2020
DOI: 10.35940/ijmh.g0683.034720
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Work Enjoyment and Work-life Balance on Organizational Citizenship Behavior with Job Satisfaction as Mediator

Abstract: The purpose of this study was to examine the effect of work enjoyment and work-life balance on organizational citizenship behavior (OCB) with job satisfaction as a mediator in property companies. This study designed an organizational citizenship behavior model, hence Model testing consists of the Outer and Inner models with the help of the Smart PLS 3.0 program. Data collection methods in the study used the scale of organizational citizenship behavior, job satisfaction, work enjoyment, and work-life balance. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
(21 reference statements)
1
0
0
Order By: Relevance
“…The efforts to minimize conflicts between work demands and life outside work encourage employees to be more willing to give their best effort. This shows that there is a link between work-life balance and organizational citizenship behavior as found by several studies (Afni & Amar, 2019;Erdianza et al, 2020;Fiernaningsih et al, 2018;Gunawan et al, 2020;Heriyadi et al, 2020;Pradhan et al, 2016;Soelton, Anees, et al, 2020;Thevanes & Harikaran, 2020). Therefore, the research hypothesis states that work-life balance has a significant positive effect on organizational citizenship behavior.…”
Section: H3 = Work-life Balance Has a Significant Positive Effect On ...supporting
confidence: 58%
“…The efforts to minimize conflicts between work demands and life outside work encourage employees to be more willing to give their best effort. This shows that there is a link between work-life balance and organizational citizenship behavior as found by several studies (Afni & Amar, 2019;Erdianza et al, 2020;Fiernaningsih et al, 2018;Gunawan et al, 2020;Heriyadi et al, 2020;Pradhan et al, 2016;Soelton, Anees, et al, 2020;Thevanes & Harikaran, 2020). Therefore, the research hypothesis states that work-life balance has a significant positive effect on organizational citizenship behavior.…”
Section: H3 = Work-life Balance Has a Significant Positive Effect On ...supporting
confidence: 58%
“…Civic virtue increases with perception of favourable conditions within the organization an indication that the organization cares about its employees (Meira & Hancer, 2021). The extant literature also suggests the influence of SWPs on civic virtue (Alnesser et al, 2022;Erdianza & Sari, 2020;Fiernaningsih, 2019). For example, in the study of organizational management, Alnesser et al (2022) found that OCB was significantly and positively related to the quality of WLB.…”
Section: Shift Work Practices (Swps) and The Dimensions Of Ocbmentioning
confidence: 99%
“…Numerous studies have been conducted to examine the link between WLB and OCB in different contexts (Erdianza & Sari, 2020;Eriyanti & Noekent, 2021;Harikaran & Thevanes, 2018;Lavanya & Sree, 2021;Mella et al, 2023). Many of these studies have established a positive association between WLB and OCB (Erdianza & Sari, 2020;Harikaran & Thevanes, 2018;Lavanya & Sree, 2021;Pradhan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations